2009
DOI: 10.3139/146.110116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of pure titanium and Ti-6Al-4V alloys with a new tailored nano/meso hybrid microstructure

Abstract: Pure titanium and Ti-6Al-4V alloy powders are treated by a mechanical milling process, which is one of the severe plastic deformation processes. The mechanical milling enables to produce a nano-grain microstructure very easily and has been applied to many powder materials. The bimodal microstructure in those mechanically milled powders is composed of a nano-grain structure with a grain size of about 50 nm in the surface-near region and of a work-hardened microstructure in the core region of the powder. We appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 8 publications
1
28
0
1
Order By: Relevance
“…[41,46,[56][57][58] The published data include those after annealing, cold rolling, or hot rolling of bulk Ti [41,46] and of bulk Ti-6 pct Al-4 pct V, [41] HPT of bulk Ti under 2 and 6 GPa, [46] equal-channel angular pressing (ECAP) of bulk Ti for 8 passes, [56,57] ECAP followed by cold rolling or cold extrusion, [56,57] accumulative roll-bonding of bulk Ti for 8 passes, [58] and of BM followed by hot roll sintering of Ti powders. [41] Solid line represents a relation delineated through the points obtained by the annealed sample and conventional cold-rolled and hotrolled samples for bulk Ti. It should be noted that, as pointed out by Zhao et al, [59] care is required for this comparison, because the ratios of the gage length to the gage width are varied from 1 to 5.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[41,46,[56][57][58] The published data include those after annealing, cold rolling, or hot rolling of bulk Ti [41,46] and of bulk Ti-6 pct Al-4 pct V, [41] HPT of bulk Ti under 2 and 6 GPa, [46] equal-channel angular pressing (ECAP) of bulk Ti for 8 passes, [56,57] ECAP followed by cold rolling or cold extrusion, [56,57] accumulative roll-bonding of bulk Ti for 8 passes, [58] and of BM followed by hot roll sintering of Ti powders. [41] Solid line represents a relation delineated through the points obtained by the annealed sample and conventional cold-rolled and hotrolled samples for bulk Ti. It should be noted that, as pointed out by Zhao et al, [59] care is required for this comparison, because the ratios of the gage length to the gage width are varied from 1 to 5.…”
Section: Discussionmentioning
confidence: 97%
“…11-Plots of ultimate tensile strength vs elongation to failure including published data for samples of pure Ti and Ti-6 pct Al-4 pct V after processing with different methods. [41,46,[56][57][58] We are also grateful to Professor H. Miura, Kyushu University, for lending us a facility of the density measurement. One of the authors (KE) thanks the Islamic Development Bank for a scholarship.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a homogeneous fine-grained structure formed by severe plastic deformation generally leads to a decrease in the ductility of metallic materials [3][4][5][6][7][8] due to the initiation of plastic instability in the early stage. Therefore, various microstructural designs have been proposed to improve both the strength and ductility of these materials [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Morita et al [9] reported that the strength of Ti-6Al-4V alloy was improved by a short-time duplex heat treatment without a reduction in ductility. In particular, we have developed a harmonic structure design [12][13][14][15][16][17][18][19], which consists of a coarse-grained structure surrounded by a network structure of fine grains, using a powder metallurgy to improve both the strength and ductility of commercially pure titanium and Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%